2004
DOI: 10.1128/jvi.78.3.1411-1420.2004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Blocking Individual Maturation Cleavages in Murine Leukemia Virus Gag

Abstract: A single protein, termed Gag, is responsible for retrovirus particle assembly. After the assembled virion is released from the cell, Gag is cleaved at several sites by the viral protease (PR). The cleavages catalyzed by PR bring about a wide variety of physical changes in the particle, collectively termed maturation, and convert the particle into an infectious virion. In murine leukemia virus (MLV) maturation, Gag is cleaved at three sites, resulting in formation of the matrix (MA), p12, capsid (CA), and nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 50 publications
2
37
0
Order By: Relevance
“…As well, there are several examples of HIV Gag mutants that form tubes, cones, and spherical cores, including deletions in the p2/SP1 spacer (19,21,22,30). Together with these findings, our data favor the interpretation that Gag molecules are capable of forming either cylindrical or spherical particles, and the regions flanking CA (p10 in RSV, p12 in Moloney MLV, and MA and SP1 in HIV) serve as "conformational switches" that provide the flexibility to allow the intermolecular rearrangements that are needed for capsid assembly (21,32,35,49,52).…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…As well, there are several examples of HIV Gag mutants that form tubes, cones, and spherical cores, including deletions in the p2/SP1 spacer (19,21,22,30). Together with these findings, our data favor the interpretation that Gag molecules are capable of forming either cylindrical or spherical particles, and the regions flanking CA (p10 in RSV, p12 in Moloney MLV, and MA and SP1 in HIV) serve as "conformational switches" that provide the flexibility to allow the intermolecular rearrangements that are needed for capsid assembly (21,32,35,49,52).…”
Section: Discussionsupporting
confidence: 69%
“…These domains are insufficient, however, to determine the normal organization of the mature virus core. Additional sequences, including CA and its flanking regions, are also necessary (21,32,35,49,52).In addition to these defined assembly domains, independent subcellular trafficking signals that provide important functions in the virus life cycle have been identified in Gag proteins. In the Gag protein of Rous sarcoma virus (RSV), there are two distinct nuclear localization signals (NLSs) within the MA and NC domains and a nuclear export signal (NES) in the p10 cleavage product located between p2 and CA ( Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A recent comparison of the region corresponding to SP1 in immature lattices of HIV, RSV, and MPMV reveals somewhat different geometries (24). However, in all retroviruses tested, including avian leukosis virus (37,38), bovine immunodeficiency virus (33), and murine leukemia virus (MLV) (16,53), as well as HIV-1, changes at or near the C terminus of the CA domain are extremely detrimental for correct particle assembly. In MLV, which does not contain a spacer between CA and NC, the C-terminal end of CA consists of an extraordinary run of charged residues, termed the "charged assembly helix" or "electric wire" motif (16).…”
Section: Discussionmentioning
confidence: 99%
“…By analogy with thermal melting studies, 99,106,107 the equilibrium melting force (F m ) may be shown to change with protein binding (ignoring double-strand binding) 23,77,99 ;…”
Section: Figurementioning
confidence: 99%